THU0010 Polymorphisms in phase i-metabolising enzyme and hormone receptor genes influence the response to anti-tnf therapy. (12th June 2018) - Canet, L.M.; Sánchez-Maldonado, J.M.; Rodríguez-Ramos, A.; Lupiañez, C.B.; Canhão, H.; Martínez-Bueno, M.; Escudero, A.; Segura-Catena, J.; Sørensen, S.B.; Hetland, M.L.; Soto-Pino, M.J.; Ferrer, M. Á.; et al.
Abstract : Background: Although the etiology of rheumatoid arthritis (RA) remains unclear, there are evidences suggesting a role of sex steroid hormones in determining the onset and progression of the disease. Objectives: The aim of this study was to evaluate whether 47 single nucleotide polymorphisms (SNPs) in steroid hormone-related genes are associated with the risk of RA and anti-TNF drug response. Methods: We conducted a case-control study in 3 European populations including 2936 RA patients and 2197 healthy controls. Of those a total of 1985 RA patients were treated with anti-TNF blockers. The association of potentially interesting markers with RA risk or drug response in the discovery population was validated through meta-analysis with data from DREAM and DANBIO registries. Results were corrected for multiple testing (Meff method; p=0.0011). The value of steroid hormone-related variants for prediction of anti-TNF drug response was also assessed using stepwise logistic regression analyses. The area under the curve (AUC) of a receiver operating characteristic (ROC) curve analysis and a −2 log likelihood ratio (LR) test were used to assess whether the genetic model fitted significantly better the data compared to the reference model. A randomization test (50.000 iterations) was run to confirm the consistency of the results. Results: Although none of the selected variants played a relevant role in modulating RA risk, the meta-analysis of the linear regression data with those from the DREAM and DANBIO registries showed a significant correlation of the CYP3A4 rs11773597 and CYP2C9 rs1799853 variants with changes in DAS28 after the administration of anti-TNF drugs (p=0.00074, and p=0.006). An overall haplotype analysis also showed that the ESR2 GGG haplotype significantly associated with a reduced chance of having poor response to anti-TNF drugs (p=0.0009). Finally, a ROC curve analysis confirmed that a model built with 8 steroid hormone-related variants significantly improved the ability to predict drug response compared with the reference model including demographic and clinical variables (AUC=0.633 vs. 0.556; P LRtest =1.52·10–6). Conclusions: These data suggest that steroid hormone-related genes play a role in determining the response to anti-TNF drugs. Disclosure of Interest: L. Canet: None declared, J. Sánchez-Maldonado: None declared, A. Rodríguez-Ramos: None declared, C. Lupiañez: None declared, H. Canhão: None declared, M. Martínez-Bueno: None declared, A. Escudero: None declared, J. Segura-Catena: None declared, S. Sørensen: None declared, M. Hetland: None declared, M. Soto-Pino: None declared, M. Ferrer: None declared, A. García: None declared, B. Glintborg: None declared, I. Filipescu: None declared, E. Pérez-Pampin: None declared, A. González-Utrilla: None declared, M. López-Nevot: None declared, P. Conesa-Zamora: None declared, A. den Broeder: None declared, S. da Vita: None declared, S. Hove Jacobsen: None declared, E. Collantes: None declared, L. Quartuccio: None declared, J. Fonseca: None declared, M. Coenen: None declared, V. Andersen Consultant for: VA has received compensation for consultancy and for being a member of an advisory board from MSD (Merck) and Janssen, R. Cáliz-Cáliz: None declared, J. Sainz: None declared